Cinema on Trial: Doctrine of Prior Restraint in Censorship - Baruah, Swagat (Christ University Law Journal, 2018)
This paper sets to address the legal question of how the Censor Board can exercise such power and whether it represents the mood and approach of the government towards films and art forms in general, in India. What history tells us is quite contrary to what we're witnessing today. Our Constitution makers, while debating on the topic of freedom of speech and expression invoked libertarian philosophers like Isaiah Berlin and John Stuart Mill, and their philosophy did in fact, find its way into the said provision. The present scenario however, is one where we have departed from these libertarian ideas. What the censor board is doing today is trying to choke the marketplace of ideas at its source, which Gautam Bhatia calls 'prior restraint' in his new book Offend, Shock or Disturb. The paper tries to establish how the law of censorship, whenever rigid, has only suppressed thought and dissent, instead of allowing progressive and rational thinking. This is substantiated by analysing various case laws.